Exploring the Job Demands–Resources Model of Work Engagement in Government: Bringing in a Psychological Perspective. (September 2019) - Borst, Rick T.; Kruyen, Peter M.; Lako, Christiaan J.
Work engagement refers to an active energetic state of mind that is characterized by vigor, dedication, and absorption. Despite practitioner's attention for work engagement, few public administration scholars have studied public servants' work engagement empirically. The goal of this study is to extend the job demands–resources (JD-R) model of work engagement using insights from the public administration literature. The analysis of a large-scale survey ( N = 9, 465) shows that (a) work and personal resources, including public service motivation, are positively related to work engagement; (b) red tape moderates these relationships; and (c) work engagement mediates the relationship between JD-R and job outcomes. In conclusion, public organizations can potentially increase work engagement and inherently employee outcomes by increasing work-related resources (autonomy, cooperation with colleagues) and selecting personnel with a proactive personality and high levels of public service motivation.